Administrative leadership and its relationship to strengthening governance in local bodies in the Palestinian governorate of Qalqilya - Ashour, Ala’ Yousef Najib (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed to examine the relationship between administrative leadership behavior and the promotion of transparency within local authorities in the Qalqilya Governorate, as well as its role in enhancing integrity. Furthermore, it investigated whether there is a correlation between administrative leadership and the enhancement of governance, and whether demographic variables (gender, educational qualification, job title, and workplace of the authority) influence this relationship. The study sought to explore the connection between administrative leadership and governance enhancement by focusing on transparency and integrity as two core dimensions in assessing governance levels. The importance of this research stems from its endeavor to understand the extent to which administrative leadership contributes to improving institutional and organizational performance in municipalities. It also examined potential statistical differences based on demographic variables. The study hypothesized the absence of significant correlations or statistically significant differences between administrative leadership and governance enhancement in light of these variables.To achieve its objectives, the researcher employed a descriptive-analytical approach using a questionnaire specifically designed for this purpose, consisting of 30 items. The questionnaire was distributed to a representative random sample drawn from the study population, which included all employees of local authorities in Qalqilya, Azzun, Jayyous, Habla, and Kafr Thulth. Based on Stephen Thompson’s equation, the sample comprised 87 male and female employees selected randomly from a total population of 113 employees. The findings revealed a high level of agreement among respondents regarding the role of administrative leadership in promoting both transparency and integrity within local authorities in the Qalqilya Governorate.